DAMPAK PERILAKU KECANDUAN GAME ONLINE PLAYER UNKNOWN’S BATTLE GROUND (PUBG) TERHADAP PRESTASI BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI LAJU REAKSI KELAS XI IPA DI SMA YAPIS MANOKWARI - Evi Dwi Dhamayanti (Universitas Papua, Manokwari, Indonesia, 2020)
Abstract Activity of playing is the Player Unknown's Battle Ground (PUBG) online game is done excessively with outrealizing it canimpact students' low learning achievement, especially chemistry subjects, which are considere ddifficult and tedious. The purpose of this study was to determine the effect of addiction behavior playing online games PUBG (Player Unknown's Battle Ground) on cognitive chemistry learning achievement of students at Yapis Manokwari Senior High School, to determine the relationship between addiction behavior playing PUBG online games (Player Unknown's Battle Ground) and cognitive learning achievement. Chemistry of students at Yapis Manokwari High School and the impact of addictive behavior on playing the Player Unknown's Battle Ground (PUBG)online game on students' chemistry learning achievement at Yapis Manokwari High School. This research uses quantitative methods with a descriptive approach. This study indicates that there is an influence of addictive behavior to play The Player Unknown's Battle Ground (PUBG) online game on the cognitive chemistry learning achievement of students at Yapis Manokwari High School. The effect was 43.8%, while the relationship between addiction behavior to play online games PUBG (Player Unknown's Battle Ground) and chemistry learning achievement was strongly correlated or correlated with 0.67.Keywords: Quantitative methods, Learning achievement, Game’s, Addiction